PEMBELAJARAN TEMATIK TERPADU DENGAN PENDEKATAN SCIENTIFIC TERHADAP MINAT BELAJAR PADA SISWA KELAS IV SD NEGERI 3 DERMOLO JEPARA - Ferina Agustini; Sihati Harles Saputri (Universitas PGRI Semarang, 2014)
Problem in this study is whether there is a relationship approach to the implementation of an integrated thematic scientific learning on student interest fourth grade 3 Dermolo Country? Goals to be achieved in this study was to find a scientific approach to the implementation of an integrated thematic learning to student interest fourth grade 3 Dermolo country. Population in this study was a public school fourth graders 3 Dermolo the number of 40 students. Samples taken were all student of class IV using sampling techniques proposive. Data were obtained through the techniques of documentation, observation, and questionnaire. Design used was a correlational design. Data analysis after treatment using a scientific approach show are as follow rcount of 0,7494 to 0,3120 rtable is that the significance level 5% so Ho rejected, then there is a significant relationship between a scientific approach to the integrated thematic learning and student interest. Can be concluded there is a relationship between the scientific approach to the integrated thematic learning and student interest. Suggestion that reserchers convey, teachers should foster student interest by using an alternative approach to learning is a scientific approach that can foster students interest in learning to be better. This can be done by getting used to package and deliver exciting learning.